Integrating Fitrah Psychotherapy into Accounting 5.0: A Rahmatan lil Alamin Approach to Islamic Boarding School Finance Behavior - Whedy Prasetyo (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study investigates how Fitrah Psychotherapy can be integrated into Accounting 5.0 to strengthen the ethical and spiritual dimensions of financial reporting in Islamic boarding schools (pesantren). The main question addressed is how fitrah-based awareness comprising intellectual, emotional, spiritual, and self-conscious dimensions can serve as a foundation for developing accounting practices aligned with rahmatan lil alamin values. The background of this issue lies in the growing challenge of balancing digital transformation with moral responsibility in the Society 5.0 era. Positioned as a conceptual and philosophical inquiry, this research draws upon Islamic psychological and accounting education perspectives to construct a model of fitrah-based financial behavior accountability. The discussion employs a qualitative reflective approach to reinterpret accounting not merely as a technical discipline, but as a psychospiritual process that harmonizes technological capability with ethical consciousness. The findings reveal that integrating fitrah psychotherapy into accounting 5.0 fosters metacompetence and multiskill learning, enabling pesantren communities to adapt technological innovations while maintaining spiritual integrity. The study concludes that fitrah-driven behavior accounting promotes human-centered financial reporting, transforming digital finance behavior education into a moral practice that contributes to inclusive and sustainable development grounded in rahmatan lil alamin.